2008
DOI: 10.1007/s11357-008-9074-z
|View full text |Cite
|
Sign up to set email alerts
|

Level of CD14+-endothelial progenitor cells is not associated with coronary artery disease or cardiovascular risk factors

Abstract: There is evidence for two subpopulations among circulating endothelial progenitor cells (EPCs), i.e., CD34 + -EPCs and CD14 + -EPCs. Prior studies on the relationship between the level of EPCs and coronary artery disease (CAD), either did not distinguish between the two types of EPCs or studied only CD34 + -EPCs. We therefore investigated whether the number of circulating CD14 + -EPCs correlates with either CAD and/or cardiovascular risk factors. Circulating CD14 + -EPCs-as defined by the surface markers CD14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
(69 reference statements)
0
6
1
Order By: Relevance
“…Mobilisation of CD14 + VEGFR-2 + monocytes following MI has been reported previously in a small clinical study by Bruno et al ,26 who also demonstrated that intramyocardial injection of CD14 + VEGFR-2 + cells improved ventricular function in a murine model of MI. By contrast, Hu et al 27 found no difference in CD14 + VEGFR-2 + cells between patients with stable or unstable CAD and healthy controls, however, this study assessed only 25 patients, 2 weeks post-ACS, and troponin concentrations were not reported making direct comparisons with our study difficult. We believe proangiogenic monocytes are mobilised in the acute response to cardiovascular stress, and may be a measure of myocardial rather than vascular or endothelial injury.…”
Section: Discussioncontrasting
confidence: 71%
“…Mobilisation of CD14 + VEGFR-2 + monocytes following MI has been reported previously in a small clinical study by Bruno et al ,26 who also demonstrated that intramyocardial injection of CD14 + VEGFR-2 + cells improved ventricular function in a murine model of MI. By contrast, Hu et al 27 found no difference in CD14 + VEGFR-2 + cells between patients with stable or unstable CAD and healthy controls, however, this study assessed only 25 patients, 2 weeks post-ACS, and troponin concentrations were not reported making direct comparisons with our study difficult. We believe proangiogenic monocytes are mobilised in the acute response to cardiovascular stress, and may be a measure of myocardial rather than vascular or endothelial injury.…”
Section: Discussioncontrasting
confidence: 71%
“…Several measures have been found to increase mobilization of PCs, such as lifestyle modification, intensifying statin therapy, cilostazol, and exercise. 31, 50,25, 26 Thus, identifying subjects at risk for PAD may allow for earlier interventions, and potentially abrogation of that risk. A low CD34+/VEGF2R+ PC cell count is indicative of worse long term prognosis, especially from vascular events.…”
Section: Discussionmentioning
confidence: 99%
“…2527 We and others have also shown that lower circulating PC levels in patients with CAD is associated with an increased risk of adverse CAD events. 28, 29 Previous studies investigating the role of PCs in diabetics with PAD found significantly decreased CD34+/VEGFR2+ cell counts and proliferation compared to healthy or diabetic subjects without PAD.…”
Section: Introductionmentioning
confidence: 92%
“…1420 Lower circulating PC counts and impaired PC activity measured by colony forming and migration assays have been reported in subjects with RFs for CVD in some but not all studies. 2123 It is also unclear in humans whether aging alters circulating PC numbers, whether exposure to the injurious effects of CVD RFs stimulates or inhibits PC, and whether presence of atherosclerotic CVD is associated with impairment of PC. Our aim was to investigate the relationship between healthy aging, and aging with exposure to CVD RFs or with established CVD, on circulating PC levels.…”
Section: Introductionmentioning
confidence: 99%